The Religious Leaders' View on Deradicalization Efforts through the Islamic Educational Institutions and Anti-Terrorism Law in Yogyakarta - M Nurul Ikhsan Saleh (Universitas Muhammadiyah Malang, 2022)
The government continues to carry out various de-radicalization efforts in responding to the phenomenon of terrorism and acts of religious-based extremism that have occurred in Indonesia in the last two decades. One of the deradicalization efforts is carried out through the application of the anti-terrorism law, although many parties are still debating the effectiveness of its enforcement. On the other hand, efforts to deradicalize the government through Islamic educational institutions need to be continued because this aspect is considered the most likely to moderate the understanding of the younger generation of Muslims. This study uses a qualitative approach, with a case study method that examines the views of religious leaders (lecturers and activist of Islamic religious organizations) on the role of Islamic educational institutions in Indonesia in the process of deradicalization and counter-terrorism. Clearly, this study reveals the need for the involvement of Islamic educational institutions in encouraging religious deradicalization programs, particularly on several aspects such as character building, moderate meaning of Islamic doctrine, understanding of the diversity of Islamic history and Fiqh, creation of comparative thought narratives, and taking appropriate action initiatives. good. Thus, this research concludes that the government needs to strengthen efforts to deradicalize through Islamic educational institutions and evaluate the effectiveness of implementing anti-terrorism laws.